A relação com o saber no processo de aprendizagem da leitura e escrita de alunos do 1º ano do ensino fundamental - Silva, Alene Mara França Sanches (2022)
The main objective of this research is to understand the relations with knowledge in the learning process of reading and writing of students in the 1st year of Elementary School of a public school located in the City of Aracaju, in Brazil. From the epistemological point of view, the research is based on Bernard Charlot’s Theory of Relation to Knowledge from the anthropological perspective, in which the problem lies in the subject's entry into an intellectual activity, i.e. in the reasons why one mobilizes and what sustains their entry into an activity. Regarding the nature of the data, this investigation is classified as qualitative. Concerning the source of information, field research was used, as well as bibliographic basis and documentary analysis. Twenty children aged between 6 and 7 years participated in this investigation. For data collection, we used Participant Observation Technique and a methodological instrument inspired by the Knowledge Balance, which we called Reading and Writing Balance. The data found were analyzed and presented in a way close to the ideal types described in Max Weber's Sociology. The results indicated the construction of three ideal types: reading and writing as a school goal (ideal type I); reading and writing as a condition for future personal life (ideal type II); reading and writing as a means of communication and information (ideal type III). The ideal types presented in this research are representative of the relationship with knowledge in the learning process of the participating public. Each dominant trend comprises the ways in which students conceived the act of learning to read and write. The results showed that ideal type I was the most dominant in the surveyed population. In their oral expressions, the children expressed that they had to learn to read and write in order to answer school tasks and get good grades. Ideal type II was evoked by the students who consider the act of learning to read and write as a form of professional achievement in adulthood. Thus, although reading and writing can be seen as mandatory by the school, the students associated this learning with the possibility of getting a job and having an income, revealing the need to learn as a means of achieving a long-term goal. Ideal type III was represented by a smaller number of students. In this trend, the children expressed that the reasons for learning were somehow associated with the social use of the language. Therefore, the meaning constructed by the students relative to the learning of reading and writing and the motives that lead them to enter into this knowledge are perceived. As historical and cultural subjects, the students re-signify their relationships with knowledge in the learning process of reading and writing based on their own experiences. Among the surveyed population, there is a strong tendency to learn for the sake of fulfilling school tasks, as a code that is needed to meet adult expectations, and not as a way of appropriating the social function of reading and writing.